Effect of planting time and vermicompost on the proteomic pattern of fenugreek (Trigonella foenum-graecum) - Mostafaie, Ali; Kahrizi, Danial; Mohammadi, Mina; Yari, Kheirollah; Rostami, Hossein; Yaghotipoor, Anita; Beheshti Ale Agha, Ali; Amjadian, Omid Ali; Yari, Peiman; Mostafaie, Hossein (Cellular and Molecular Biology, 2018)
The fenugreek is one of the most important medicinal plants belongs to Fabaceae, originated in West Asia, Iran and Mediterranean regions. This research included a qualitative study of fenugreek proteins using SDS-PAGE electrophoresis on polyacrylamide gel and the separation of protein bands of fenugreek leaves in different treatments of vermicompost fertilizer and cultivating dates. Results showed that a band (about 80 kDa) on the first planting date (May 31) is observed in all samples except for sample a1 (10 t/ha vermicompost on May 31). Another significant difference was the band contained in the third planting date (31 September) and in the molecular weight of about 15 kDa, which was not seen in other dates. This difference can be due to the synthesis of this protein with the mentioned weight under the conditions of reducing the temperature in the early fall. It also showed more differences in two-dimensional electrophoresis, for example, in 14 kDa and PI in the range of 4.5-4.7 in treatment without fertilizer, no protein expression was observed, which was consistent with the results of the SDS-PAGE test.